Dhikr as a Psychospiritual Therapy for the Elderly: A Phenomenological Study at the Ibnu Masud Elderly Boarding School, Segamat, Johor, Malaysia - Sukandar, Warlan (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2025)
This study aims to explore and describe the subjective experiences of elderly individuals in practicing dzikir as a form of psychospiritual therapy at Madrasah Ibnu Masud, Segamat, Malaysia. Using a qualitative approach with a phenomenological design, the study involved five elderly informants who actively participated in morning and evening dzikir sessions. The research data were collected through three methods: in-depth interviews, observation, and documentation, which served to complement and strengthen the primary data. The collected data were analyzed through three stages: data reduction, data display, and conclusion drawing and verification. The results of the study revealed five main themes: inner peace and anxiety reduction, spiritual connection and meaning of life, emotional regulation enhancement, reactualization of self-worth, and spiritual loneliness therapy. These findings indicate that dzikir is not merely a ritual worship practice, but also serves as an effective psychospiritual therapy that enhances the mental health and emotional well-being of the elderly. Dzikir has a significant impact in strengthening spiritual connection, improving emotional conditions, and reconstructing life meaning and self-esteem in the elderly. This study recommends the integration of dzikir practices into elderly care programs as a low-cost, meaningful, and faith-based approach